MARKETING STRATEGY OF BROILERS AT CV CIKIJING FARM, SIDOARJO DISTRICT - Ari Susanto (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
Effective marketing strategies are vital for the success and sustainability of businesses. This study investigates the marketing strategies employed by CV Farm Cikijing, a broiler business seeking to achieve long-term growth and stability. The research adopted a quantitative approach, utilizing survey and interview methods to gather data from the company. Through the application of the IE matrix, the marketing position of the chicken farm business was determined to be in Quadrant V, indicating a phase of growth and stability. To ensure sustainable growth, the study recommends a combination of strategic approaches, including market penetration, market development, and diversification of processed chicken products. These strategies aim to enhance the company's market presence, capitalize on existing markets, and explore new opportunities. The findings of this research hold valuable insights for businesses in the poultry industry and beyond, emphasizing the significance of well-planned marketing strategies in achieving long-term success and resilience in a competitive market landscape. By identifying and implementing suitable marketing approaches, businesses can navigate challenges, optimize growth, and secure a strong foothold in the market.